Examining the Effects of Life Expectancy and Expectations for Future Health on Adolescent Suicidal Behavior. Issue 4 (3rd April 2022) - Posick, Chad; Zimmerman, Gregory M.
ABSTRACT: Research has linked various constructs with a shared focus on the future to suicidal behavior. This study examined: (1) whether life expectancy and expectations for future health were associated with reduced odds of suicidal ideation and attempted suicide, and (2) whether the reducing effect of having high levels of future expectations on suicidal ideation was stronger among individuals with lower levels of depression. Study participants were youths from the National Longitudinal Study of Adolescent to Adult Health (Add Health), a multi-wave panel study of how individual, family, peer, and school factors contributes to youth developmental outcomes. Sequential logistic regression models on 14, 644 youths (average age = 14.7 years; 51.3% female; 58.7% white) indicated that higher reported levels of life expectancy and expectations for future health were associated with reduced odds of engaging in suicidal ideation and attempted suicide, net of an array of well-established correlates of suicidal behavior. Depression moderated this relationship such that the association between future expectations and suicidal behavior was amplified among youths with lower levels of depression. The findings suggest that interventions that address suicidal thoughts and actions should promote positive thinking about the future.